Irwan Prayitno and the Mass Media: A Transitivity Analysis of News Reporting in Padang Ekspres - Hetti Waluati Triana; Reflinaldi Reflinaldi; Awliya Rahmi (Masyarakat Linguistik Indonesia Universitas Andalas, 2020)
This article attempts to analyze the transitivity pattern in the media discourse analysis of Irwan Prayitno's reportage in Padang Ekspres. The study was conducted using a qualitative approach. Data were collected using documentation techniques and analyzed using the transitivity features on Halliday's Systemic Functional Linguistics. The research findings show that there are four types of processes in the media discourse of Irwan Prayitno’s reportage in Padang Ekspres: material processes (50.8%), behavioral processes (22.1%), verbal processes (20.4%), and mental processes (6.7 %). The dominance of material processes in Irwan Prayitno's reportage as a political figure reflects an effort to represent him as a leader who focuses on real work and action. This representation pattern also strengthens the existence of mutualistic relations between mass media and politics in electoral politics and other kinds of mass mobilization.